A rubric and methodology for benchmarking referral goals. Issue 1 (12th February 2018) - Ward, David; Jacoby, JoAnn
Abstract : Purpose: This paper aims to identify more advanced criteria for identifying referral opportunities and improve understanding of when to refer through developing and defining distinct question categories and related criteria. Design/methodology/approach: Chat transcripts were analyzed and coded using a rubric developed on the basis of published research and original criteria developed for the study. Coding focused on whether a referral was made, if an opportunity was missed (termed "referral gap"), and what factors influenced its presence or absence. Findings: Quantitative and qualitative factors that influence when referrals are successfully made were identified. Questions higher on the reference effort assessment data scale and those relating to subject-based research tended to have a higher referral gap, while the presence of instruction in evaluating resources had a positive impact on referrals being made. Recognizing patron-based factors such as knowledge of library policies also impacted the presence of referrals. Research limitations/implications: Limitations include the data, which were taken from a single institution and primarily reflect questions occurring in academic libraries. Practical implications: Suggestions are provided for training and reference management approaches to improve the presence, substance and quality of referrals. Originality/value: The study introduces a new measure for evaluating referrals, termed the "referral gap." The methodology also expands on traditional data points used to measure when referrals should occur, which typically focus on patron and staff affiliations.